Pelatihan Pembuatan Terarium Sebagai Produk kewirausahaan Bagi Siswa SMA Negeri 1 Sindang Danau Kabupaten Oku Selatan - Rosanti, Dewi (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Formal school education institutions, one of which is Senior High School (SMA/SMK/MA) both public and private, which is in the process of achieving success in the teaching and learning process, are currently starting to implement entrepreneurship programs for students, especially since the Covid pandemic -19 hit. South Ogan Komering Ulu Regency (OKUS) is one of the districts in the province of South Sumatra, administratively located on the Sumatran highway so that the development of this district continues to progress. Various educational institutions both private and public, including SMAN 1 Sindang Danau. This PkM program aims to provide information for students and teachers in making terrariums as entrepreneurship learning based on science lessons. The activity was carried out on October 20 2022 at SMAN 1 Sindang Danau, OKU Selatan Regency. The implementation method is done by direct simulation. The results achieved by students of SMAN 1 Sindang Danau can apply terrarium making techniques as an application of science learning.